ANALYZING OF SYSTEM USABILITY SCALE IN USER EXPERIENCE EVALUATION OF DANA APPLICATIONS - Fuaida, Famrotul; Prasojo, Bayu Hari; Racmadany , Andry; Almanfaluti , Istian Kriya (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The rapid development of financial technology (FinTech) has transformed how individuals conduct financial transactions, particularly through e-wallets. Dana, one of the leading e-wallet applications in Indonesia, has garnered significant attention due to its widespread usage and user feedback. Method: This study evaluates the user experience (UX) of the Dana application using the System Usability Scale (SUS) that provides a quick and quantitative measure of usability, Data were collected from 153 respondents through a questionnaire. Results: The SUS analysis yielded an average score of 65. According to SUS interpretation scales, this score categorizes Dana as